2019
DOI: 10.1002/admi.201901193
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Impact of Charge Selective Contact in Halide Perovskite through Impedance Spectroscopy

Abstract: paved the way for new formulations by the means of compositional engineering of perovskites. [1] Tweaking of halide anion and/or organic cation allowed to push the efficiency as well as stability. [2] Power conversion efficiencies as high as 25.2% have been reported at laboratory scale, [3] which is on par with other matured thin film photovoltaics (PV) technologies. The realization of perovskite for PV application was due to its intriguing optoelectrical properties, which led to its exploitation in other opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 60 publications
0
25
0
Order By: Relevance
“…Moreover, the FF also decreases due to the higher R s value in the absence of HTM. Similarly, Khan et al [68] also performed a study on the impact of HTM layer in PSCs by EIS technique which also showed a lower recombination resistance in the case of HTM-free PSC devices.…”
Section: Use Of Eis For the Comparison Of Htm-based And Htm-free Pscsmentioning
confidence: 93%
“…Moreover, the FF also decreases due to the higher R s value in the absence of HTM. Similarly, Khan et al [68] also performed a study on the impact of HTM layer in PSCs by EIS technique which also showed a lower recombination resistance in the case of HTM-free PSC devices.…”
Section: Use Of Eis For the Comparison Of Htm-based And Htm-free Pscsmentioning
confidence: 93%
“…From the derivative of the capacitance spectrum (Figure S16, Supporting Information), we determined the frequency of peak emission ( f peak ) rate of electrons from a trap state located below E T to the LUMO edge E LUMO as depicted schematically in Figure . From the slope of Arrhenius plot, ln fpeakT2 vs.1T, the value of activation energy E A , and attempt to escape frequency υ 0 were deduced through the relation:38 lnν0T2 = lnβ−EAkBT where β is a proportionality constant, T is the temperature, and k B is the Boltzmann constant. The calculated activation energy for each device are presented in Table 1 .…”
Section: Defect Spectroscopymentioning
confidence: 99%
“…From the slope of Arrhenius plot, ln . 1 peak 2 f T vs T , the value of activation energy E A , and attempt to escape frequency υ 0 were deduced through the relation: [38] ln ln…”
Section: Defect Spectroscopymentioning
confidence: 99%
“…, the value of activation energy EA, and attempt to escape frequency 0 were deduced through the relation: [38]  …”
Section: Defect Spectroscopymentioning
confidence: 99%